Gendered Impact of Labor Migration: A Study on the Left-Behind Wives’ Decision-Making Abilities in Bangladesh - Halim, Abdul; Riya, Subata Zannat (International journal of multicultural and multireligious understanding, 2025)
This study examines the complex relationship between male labor migration and women's empowerment in Bangladesh, with a focus on the decision-making abilities and autonomy of left-behind wives. In patriarchal societies, men typically dominate household decisions, but their migration offers women opportunities for increased independence and responsibility. However, this shift is complex, as women often remain dependent on their husbands for emotional and economic support, and men continue to influence decisions remotely. Being done from a qualitative methodology and using the ‘empowerment theory’ of Naila Kabeer, this study reveals that multiple intersecting factors beyond access to remittances and education influence women’s empowerment. Geographic origin, family structure, and persistent patriarchal norms significantly impact wives' ability to make autonomous decisions. While some women, particularly in nuclear families, gain increased control over resources and decision-making, others face restricted mobility and limited control over remittances, especially in extended families. The research also reveals emerging opportunities for economic independence through home-based businesses, which are often constrained by gender-based wage discrimination and social restrictions. These findings contribute to a deeper understanding of how transnational migration intersects with existing social structures to shape women's empowerment in patriarchal societies.